Hepatitis B vaccination and occupation exposure in the healthcare sector in Belo Horizonte, Minas Gerais - Assunção, Ada Ávila; Araújo, Tânia Maria de; Ribeiro, Rafael Brito Nery; Oliveira, Sérgio Vinícios Soares (Revista de Saúde Pública, 2012)
OBJECTIVE: To identify factors associated with vaccination against hepatitis B among healthcare workers. METHODS: This was a cross-sectional study on 1,808 public-sector healthcare workers in Belo Horizonte, Southeastern Brazil, in 2009. A self-administered questionnaire was used and the vaccination situation was analyzed taking sociodemographic characteristics, lifestyle and working conditions and characteristics into consideration. Univariate (p < 0.20) and multiple (p < 0.05) statistical analyses were performed using Poisson regression to evaluate factors associated with vaccination. RESULTS: Of the workers, 85.6% declared that they had been vaccinated, although only 74.9% of the vaccinated professionals had received a complete imunization schedule. Not having been vaccinated was associated with not having a partner; having high school, technical or incomplete higher education level; work characteristics such as working in surveillance or the administrative/general services sector; and not using personal protection equipment. CONCLUSIONS: Groups with lower vaccination coverage were identified. Efforts are required to ensure access and adherence to vaccination among healthcare workers, such as awareness-raising mechanisms.